Taking Sides Clashing Views on African issues - Moseley, William G. (New York McGraw Hill, 2012)
Taking Sides: Clashing views on African Issues, Fourth edition, is a debate-style reader designed to introduce students to controversies in African studies. The readings, which represent the arguments of leading scholars and commentators, reflect opposing positions and have been selected for their liveliness and substance and because of their value in debate framework. For each issues, the editor provides a concise introduction and postscript summary. The introduction sets the stage for debate as it is argued in the "yes" and "no" readings. The postscript briefly reviews the opposing opinions and suggests additional readings on the controversial issue under discussion. By requiring students to analyze contradictory positions and reach considered judgments, Taking sides actively develops students critical thinking skills. It is this development of critical thinking skills that is the ultimate purpose of each of the volumes in the widely acclaimed taking sides program.
Keywords: History, Development Agriculture Social Issues Governance